Digital Censorship and The Transnational Strengthening of Political Activism in Thailand and Southeast Asia - Syifa Aulia Jasmine; Sugito (Universitas Negeri Yogyakarta, 2026)
This study examines how digital censorship shapes political expression and online activism in Thailand, with attention to emerging transnational influences in Southeast Asia. It explores how legal restrictions affect communication practices and how activists adapt under surveillance and legal uncertainty. Using qualitative case study approach, the research analyze 150 purposively selected Twitter (X) posts, legal documents including the Computer Crime Act and Article 112 of the Thai Criminal Code, and over 20 secondary reports from NGOs and media. The findings reveal that state-imposed social media restrictions produces a strong chilling effect, lead to self-censorship and indirect, symbolic political expression. Activist use coded language, memes, hashtags, and meaning-making. This study concludes that despite increasing repression, online political engagement in Thailand remains active, resilient, and evolving. The research highlights the urgent need to safeguard digital rights and freedom of expression in emerging democracies